2019
DOI: 10.29252/jrds.16.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of antifungal effect of aqueous extract of garlic on Candida albicans (INVITRO)

Abstract: Background and aim: Candidiasis is a common fungal disease in the mouth. An appropriate treatment for candidiasis is the use of antifungal drugs. Due to drug resistance and known side effects of drugs, the tendency to use medicinal herbs is increasing. Garlic is identified as a strong antibacterial. Therefore, in this study, the effect of aqueous garlic extract and nystatin on Candida albicans was investigated.Materials and Methods: An experimental study was carried out. For each control and case group, one st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Thus, GE could be regarded as a better alternative in treating denture stomatitis [ 68 ]. Likewise, in vitro study the antifungal effect of AGE on C. albicans was investigated and they found that it was able to inhibit the growth of C. albicans, but its effect was less than nystatin [ 69 ].…”
Section: Bioactivities Of Ge In Alleviating the Oral Pathologiesmentioning
confidence: 99%
“…Thus, GE could be regarded as a better alternative in treating denture stomatitis [ 68 ]. Likewise, in vitro study the antifungal effect of AGE on C. albicans was investigated and they found that it was able to inhibit the growth of C. albicans, but its effect was less than nystatin [ 69 ].…”
Section: Bioactivities Of Ge In Alleviating the Oral Pathologiesmentioning
confidence: 99%
“…(21) An investigation has shown the effect of aqueous garlic extract on Candida albicans (C. albicans) in the mouth. (22) The results of the cited study showed that the aqueous extract of garlic was able to inhibit the growth of C. albicans but its effect was less than that of nystatin. (22) Further research using different extraction methods and concentrations is suggested…”
Section: Mean±sd CV (%)mentioning
confidence: 99%
“…It has been known to have hair growth stimulating properties 9 . Garlic ( Allium sativum ) from family Liliaceae has a wide range of medicinal properties, 10 it has antibacterial, 11 antiviral, 12 antifungal, 13 and antiprotozoal properties 14 . The main pharmacological effect of garlic is referred to presence of organosulfur volatile compounds, especially allicin which is produced when the garlic bulb is crushed 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, allicin has an immunomodulatory effect by enhancing the activity of macrophage during infection 22 . Moreover, it has antifungal properties against Candida albicans and antiprotozoal properties against amoeba parasite 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation